1995
DOI: 10.1161/01.cir.92.7.1883
|View full text |Cite
|
Sign up to set email alerts
|

Superficial Accumulation of Plasminogen During Plasma Clot Lysis

Abstract: We conclude that the generation of potent surface-associated plasminogen-binding sites during thrombolysis results in a strikingly high plasminogen concentration at the dynamically changing surface of a lysing clot. The necessity of a continuous plasminogen supply from the plasma supports the use of fibrin-specific and plasminogen-sparing agents for thrombolytic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
110
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(122 citation statements)
references
References 50 publications
11
110
1
Order By: Relevance
“…3b). The correlation coefficient (r ¼ 0.734) confirmed a sound concurrence with confocal microscopy studies of model clots in vitro, where platelets were shown to impede the transport of thrombolytics into the clot (24,27). The correlation could serve for estimation of thrombolysis outcome if the initial platelet proportion is known.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…3b). The correlation coefficient (r ¼ 0.734) confirmed a sound concurrence with confocal microscopy studies of model clots in vitro, where platelets were shown to impede the transport of thrombolytics into the clot (24,27). The correlation could serve for estimation of thrombolysis outcome if the initial platelet proportion is known.…”
Section: Discussionsupporting
confidence: 71%
“…Thrombolysis is retarded in platelet-rich regions due to the tight platelet connections by means of glycoprotein receptors (GP IIb/IIIa) and fibrinogen as well as by the lack of serum containing plasminogen (22)(23)(24)(25). On the contrary, thrombolysis is more efficient in RBC-rich regions, which have a loose fibrin network with abundant extracellular space filled with serum (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Recent structural studies have emphasized that fibrin digestion proceeds locally by transverse cutting across fibers rather than by progressive cleavage uniformly around the fiber and that changes of the fibrin network structure are spatially restricted to a zone in which high accumulation of fibrinolytic components takes place. [7][8][9][10] However, none of these findings provide sufficient conclusions regarding the impact of the fibrin network structure and the fibrin fiber diameter on fibrinolysis speed.…”
mentioning
confidence: 99%
“…Therefore, even though more HE-SAKK (33 kDa) can be trapped inside the clots in proportion to the amounts of fibrin- bound thrombin, those HE-SAKK molecules located in the interior of the clot would not be able to activate plasminogen. This is simply because plasminogen is too big to diffuse into the interior of the clot as illustrated by the superficial accumulation of plasminogen only on the clot surface in the confocal microscopic study (52). In comparison with fibrin clots formed under in vitro conditions, it is logical to predict that HE-SAKK would be able to lyse the freshly formed pathologic thrombi more efficiently.…”
Section: Reshuffling Of Disulfide Bonds In Hirudin-e Coil and He-sakk-bmentioning
confidence: 98%